Mode of Transmission, Rather than the Hepatitis C Virus, as a Major Determinant of Poor Interpersonal Relationships in Patients with Chronic Hepatitis C - Thuy Phuong La; Marc Deschênes (Canadian Journal of Gastroenterology)
BACKGROUND: Recent studies have demonstrated that patients with the hepatitis C virus (HCV) have significant neurocognitive impairment.